Practice of analgesia and sedation in adult mechanically ventilated patients in South African ICUs - Hendricks, Nicole Emaline (My University, 2020)
Background Pain and agitation are experienced in the intensive care unit (ICU) during mechanical ventilation. There is a move toward analgesia and away from sedation to avoid the negative sequelae of sedation and to ensure a calm, comfortable patient. The ICU practice of analgesia and sedation have been described internationally, but not in South Africa. Objectives The aim of this study is to describe the practice of analgesia and sedation by doctors in adult mechanically ventilated patients in ICUs in South Africa. Methods This study used a descriptive, prospective, contextual study design. A convenience sampling method was used with distribution of a questionnaire at the Critical Care Society of Southern Africa congress in 2018. Results- The Visual Analog Scale (VAS) and the Richmond Agitation-Sedation Scale (RASS) were the most used scales for analgesia and sedation assessment, respectively. Morphine was the drug most used for both analgesia and sedation. The benzodiazepine midazolam was the second most used sedative (31%). Non-pharmacological methods were used by 26.4% of respondents. Patients’ clinical diagnosis was the main factor influencing the selection of analgesics and sedatives, which equated to 65.2% and 74.6%, respectively. Conclusion Analgesia and sedation assessment are performed by most doctors. Morphine is still commonly used, but the use of midazolam remains high despite evidence for its negative sequelae. These practices in ICU may be improved by training doctors in the assessment of patients, drug selection and the implementation of analgesia and sedation guidelines.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020